The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1121/1.2747157
|View full text |Cite
|
Sign up to set email alerts
|

Transmission matrix analysis of the chinchilla middle ear

Abstract: Despite the common use of the chinchilla as an animal model in auditory research, a complete characterization of the chinchilla middle ear using transmission matrix analysis has not been performed. In this paper we describe measurements of middle-ear input admittance and stapes velocity in ears with the middle-ear cavity opened under three conditions: intact tympano-ossicular system and cochlea, after the cochlea has been drained, and after the stapes has been fixed. These measurements, made with stimulus freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 34 publications
3
38
0
Order By: Relevance
“…Another potential reason for these differences at high frequency is that Ruggero et al ͑2007͒ measured velocity of the lenticular process, and added gains measured across the incudo-stapedial joint, whereas we measured velocity from locations on the footplate and parts of the crura close to the footplate. Mean, SNR > 20 dB (this study) 95% Confidence Interval 10 dB < SNR < 20 dB Décory, 1989;Décory et al, 1990 Chinchilla (this study) Cat (Décory, 1989; Gerbil (Olson, 2001) Guinea Pig (Décory, 1989) Human (Puria et al, 1997) FIG We compared our measured Z C with previous estimates in chinchilla by Ruggero et al ͑1990͒ andRosowski ͑2007a͒. Our Z C is a more direct estimate than either of these previous studies because we derived Z C from simultaneous measurements of P V and V S whereas ͑1͒ Ruggero et al ͑1990͒ combined their own V S measurements ͑see Fig.…”
Section: E Comparison With Other Studies In Chinchillamentioning
confidence: 88%
See 1 more Smart Citation
“…Another potential reason for these differences at high frequency is that Ruggero et al ͑2007͒ measured velocity of the lenticular process, and added gains measured across the incudo-stapedial joint, whereas we measured velocity from locations on the footplate and parts of the crura close to the footplate. Mean, SNR > 20 dB (this study) 95% Confidence Interval 10 dB < SNR < 20 dB Décory, 1989;Décory et al, 1990 Chinchilla (this study) Cat (Décory, 1989; Gerbil (Olson, 2001) Guinea Pig (Décory, 1989) Human (Puria et al, 1997) FIG We compared our measured Z C with previous estimates in chinchilla by Ruggero et al ͑1990͒ andRosowski ͑2007a͒. Our Z C is a more direct estimate than either of these previous studies because we derived Z C from simultaneous measurements of P V and V S whereas ͑1͒ Ruggero et al ͑1990͒ combined their own V S measurements ͑see Fig.…”
Section: E Comparison With Other Studies In Chinchillamentioning
confidence: 88%
“…The effect of the hole was smaller as frequency increased, with less than a 3 dB difference by 1 kHz in both the experimental and predicted data. Nonetheless, the detailed shape of the predicted change in ͉P V ͉ is different from the measured change, where much of the differences come from frequency-dependent variations in Z C and Z out that originate in the details of the data used in their calculation ͑Songer and Rosowski, 2007a͒. As for the phase, the ϳ0.15 cycles increase predicted by the model at 150 Hz is consistent with the experimental data around this frequency, but the measured and predicted changes differ slightly at other frequencies.…”
mentioning
confidence: 99%
“…*Although middle-ear transmission has not been measured in macaques, studies in other mammals suggest that delays attributable to round-trip middle-ear transmission appear negligible compared with traveling-wave delay (29)(30)(31). † Otoacoustic delays and neural tuning in guinea pigs and chinchillas are generally similar to those in cats (17,20).…”
Section: Auditory-nerve Tuning In Macaques Is Sharper Than In Commonmentioning
confidence: 97%
“…Initial studies (Songer and Rosowski 2007;Ruggero et al 1990) could not ascertain the highfrequency limit of the transfer function of the chinchilla middle ear because of technical limitations but more recent studies concluded that middle-ear transmission determines the high-frequency cutoff of the audiogram Ravicz et al 2010;Ravicz and Rosowski 2013a, b). The first purpose of the present investigation was to extend our previous measurements of the bandwidth of stapes vibrations in chinchilla ) taking advantage of improved acoustic-stimulus and velocity-recording systems.…”
Section: Introductionmentioning
confidence: 99%